Effect of irrigation and intercropping system on yield, water-use, concentration and uptake of nitrogen, phosphorus and potassium in maize (Zea mays)and groundnut (Arachis hypogaea) grown as sole and intercrop - SAREN, B K; JANA, P K (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was conducted during summer season of 1990 and 1991 on intercropping maize (Zea mays L.)and groundnut (Arachis hypogaea L.) on a well-drained sandy-loam soil under 4 levels of irrigation. Intercrop maizegave slightly higher yield (3.2-5.8%) compared with the sole maize; 1 146 and 946 kg/ha extra kernel yield of intercropgroundnut at 1 : 2 and 2 : 3 row ratio respectively. Intercrop of groundnut yielded lower than the sole groundnut.Irrigation increased yield of maize, groundnut and total yield in terms of maize equivalent, consumption use of solemaize, sole groundnut and their mixture of 1 : 2 and 2 : 3 ratio were 29.6, 28.8, 30.0 and 31.2 cm respectively.Consumptive-use efficiency was greater in intercropping systems than sole crop. Intercropping increased NPK uptakein stalk, kernel, husk and whole plant of groundnut while K uptake enhanced in stover in maize. Total NPK uptake bymaize + groundnut was also greater in intercropping system. Irrigation increased NK uptake in maize stover andaugmented NPK uptake in different parts of groundnut plant except NK uptake in stalk. Total NPK uptake by maize +groundnut increased with irrigation and maximum NP uptake being at 2 irrigation and K uptake at 1 irrigation.